Undifferentiated duodenal sarcoma with rhabdoid features - Parag J. Karkera; Pradnya S. Bendre (Elsevier, 2020)
Tumors of the pediatric gastrointestinal tract are uncommon, with duodenal malignancies being extremely rare. Malignant rhabdoid tumor is a rare highly aggressive tumor that occurs in young children with a very poor clinical outcome. The tumor is characterized by a diffuse proliferation of "rhabdoid cells," which are round or polygonal with eccentric nuclei, prominent nucleoli, and glassy eosinophilic cytoplasm containing hyaline-like inclusion bodies. Very few cases of malignant tumors with rhabdoid features of the gastrointestinal tract are described in literature, but probably none so far in the duodenum of a pediatric patient. We present a case of a eleven year old with an undifferentiated tumour of the duodenum with rhabdoid features on histopathology, who underwent multimodality management and is doing well at 1 year of follow up.